К вопросу о концепциях судебного правоприменения - Личман, Леонід Григор'євич; Личман, Леонид Григорьевич; Lichman, Leonid (My University, 2012)
The article is devoted to the exposure of the most ponderable conceptions of application of law, represented in scientific literature and periodicals. On the basis of analysis of scientific sources and current legislation of Ukraine a conclusion about naturalness of transformation of conception of application of law in modern terms is formulated, that in opinion of author is determined by the changes in application of law, taking place for the last decades, and also changes of the valued constituents understanding of law is right in consciousness of modern.
Личман Л. Г. К вопросу о концепциях судебного правоприменения / Л. Г. Личман // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 140-150.
Keywords: правоприменение; концепции правоприменения; правопонимание; гражданское судопроизводство; принципы судопроизводства; судебная практика; судейское усмотрение; правозастосування; концепції правозастосування; праворозуміння; цивільне судочинство; принципи судочинства; судова практика; суддівський розсуд; application of law; conceptions of application of law; understanding of law; civil legal proceeding; principles of the legal proceeding; judicial practice; judge discretion